2020
DOI: 10.3390/biomedicines8020029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anchomanes difformis on Inflammation, Apoptosis, and Organ Toxicity in STZ-Induced Diabetic Cardiomyopathy

Abstract: Persistent hyperglycemia is known to cause enhanced generation of reactive oxygen species in diabetes. Several inflammatory cytokines are induced by oxidative stress, and their release also leads to increased oxidative stress; this makes oxidative stress one of the important factors in the development of chronic inflammation and other immune responses. These have been implicated in the development of diabetic complications such as nephropathy and cardiomyopathy. Anchomanes difformis has been shown to possess a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 61 publications
3
14
0
Order By: Relevance
“…In this study, diabetic rats presented momentously raised in MDA probably due to accumulation of free radicals which might lead to DNA fragmentation and protein damage of the heart tissue. This is in accordance with the previous study carried out by Alabi et al 17) . However, this was ameliorated in diabetic rats that received ST leaf (LDST and HDST) probably due to its antioxidant ability.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, diabetic rats presented momentously raised in MDA probably due to accumulation of free radicals which might lead to DNA fragmentation and protein damage of the heart tissue. This is in accordance with the previous study carried out by Alabi et al 17) . However, this was ameliorated in diabetic rats that received ST leaf (LDST and HDST) probably due to its antioxidant ability.…”
Section: Discussionsupporting
confidence: 94%
“…1. Persistent hyperglycemia stimulates the generation of ROS and reactive nitrogen species (RNS) in the heart mitochondria 17) . Surplus ROS support rises in lipid peroxidation (MDA) and subsequently changes membrane structure and enzyme activities 18) .…”
Section: Discussionmentioning
confidence: 99%
“…The diabetic model mice in the present study exhibited increased serum levels of IL-12 and IL-6 and increased mRNA levels of IL-12 and IL-6 in the heart. In line with previous studies showing that the cardiac level of IL-10, an important anti-inflammatory cytokine, significantly decreased in diabetic animals [ 45 , 46 ], we found that the serum level of IL-10 significantly increased in diabetic mice. These data indicate that the imbalance between the proinflammatory cytokines and anti-inflammatory cytokines plays a vital role in DCM, and the rebalance of the inflammatory level might have direct cardioprotective effects on diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…The wide range of biological properties of compounds present in AD has necessitated the need to further investigates its potentials against diabetes and diabetic complications. Our research works then investigated, established and reported the antidiabetic ability of AD aqueous extract [ 27 ], which led to further explore the attenuating ability of AD diabetic complications involving the liver, heart and the reproductive system [ 27 , 28 , 29 ]. However, no study has been conducted to investigate the potency of AD leaves on the kidney and pancreas pathology in diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%